2019
DOI: 10.1159/000500042
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Treatment of Chronic Kidney Disease-Related Metabolic Acidosis Reduces Cardiovascular Risk Better than Sodium Bicarbonate

Abstract: Background: Current guidelines recommend treatment of metabolic acidosis in chronic kidney disease (CKD) with sodium-based alkali. We tested the hypothesis that treatment with base-producing fruits and vegetables (F + V) better improves cardiovascular disease (CVD) risk indicators than oral sodium bicarbonate (NaHCO3). Methods: We randomized 108 macroalbuminuric, matched, nondiabetic CKD patients with metabolic acidosis to F + V (n = 36) in amounts to reduce dietary acid by half, oral NaHCO3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 50 publications
4
76
0
4
Order By: Relevance
“…Randomization for three years to usual care or interventions designed to reduce dietary acid by 50%, using either sodium bicarbonate include age, eGFR, total energy intake, physical activity, smoking status, alcohol intake, BMI, CVD history, blood pressure, antihypertensives and lipid lowering medication or alkali-rich fruits and vegetables [9] resulted in similar control of metabolic acidosis and eGFR preservation and to a greater extent than usual care. Of note, a 5-year extension of the follow up of this trial [53] not only confirmed these findings, but also showed that the group receiving fruits and vegetables had better systolic blood pressure and body mass index control, improved lipid profile and higher serum levels of vitamin K 1 than those under bicarbonate therapy or usual care [53].…”
Section: Discussionsupporting
confidence: 62%
“…Randomization for three years to usual care or interventions designed to reduce dietary acid by 50%, using either sodium bicarbonate include age, eGFR, total energy intake, physical activity, smoking status, alcohol intake, BMI, CVD history, blood pressure, antihypertensives and lipid lowering medication or alkali-rich fruits and vegetables [9] resulted in similar control of metabolic acidosis and eGFR preservation and to a greater extent than usual care. Of note, a 5-year extension of the follow up of this trial [53] not only confirmed these findings, but also showed that the group receiving fruits and vegetables had better systolic blood pressure and body mass index control, improved lipid profile and higher serum levels of vitamin K 1 than those under bicarbonate therapy or usual care [53].…”
Section: Discussionsupporting
confidence: 62%
“…These data should be interpreted with caution since these studies were not primarily designed to address the metabolic effect of these diets and included different levels of protein restriction. Base-providing diets tend to have a high potassium content and hence participants in these studies were carefully selected to be at very low risk to develop hyperkalemia (11,13,14). Further, willingness to adhere to a restrictive diet is a challenging factor in dietary intervention studies in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of included trials (n=6) in this earlier report, along with a limited number of patients, precluded definitive conclusions regarding the risks and benefits of oral alkali supplementation. Subsequently, longer-term prospective trials have examined the effect of intervention with oral alkali supplementation (e.g., sodium bicarbonate or sodium citrate) (10)(11)(12)(13)(14)(15) or dietary intervention (e.g., diets enriched with fruits and vegetables or very-low-protein diets supplemented with ketoanalogues, both designed to reduce the intake of dietary acids) (11)(12)(13)(14)16) on kidney disease progression and other surrogate outcome measures. To summarize the current evidence on this topic, we performed a systematic review and meta-analysis examining the effect of oral alkali supplementation or dietary intervention compared with no treatment, usual care, or placebo, in patients with stage 3-5 CKD and metabolic acidosis and low-normal serum bicarbonate levels.…”
Section: Introductionmentioning
confidence: 99%
“… 41 In patients with CKD and metabolic acidosis, increased fruit and vegetable consumption over 5 years was associated with improvements in CVD risk factors, including body mass index, systolic BP, and low-density lipoprotein, lipoprotein(a), and serum vitamin K levels. 42 A National Health and Nutrition Examination Survey study showed that a diet high in plant-based protein was associated with lower risk for mortality, 43 and in a small study of patients with moderate CKD, a reduced-sodium DASH diet for 2 weeks led to improvements in nocturnal diastolic BP and was not associated with hyperkalemia. However, in the latter study, mean serum potassium levels showed a transient increase after 1 week of the DASH diet (change from baseline, +0.07 ± 0.01 mEq/L; P = 0.04) that was not significant after 2 weeks (+0.04 ± 0.07 mEq/L; P = 0.13).…”
Section: Potential Benefits Of a Plant-based Dietmentioning
confidence: 99%